Upconversion luminescence mechanisms of Er3+ ions under excitation of an 800 nm laser. Issue 17 (7th May 2015) - Shang, Xiaoying; Chen, Ping; Jia, Tianqing; Feng, Donghai; Zhang, Shian; Sun, Zhenrong; Qiu, Jianrong
<x xml:space="preserve">Abstract</x> The green/red emission mechanisms of Er3+ ions are studied by comparing PL properties upon excitation by CW and fs lasers.